Bioelectronic Interfaces: Inkjet‐Printed Flexible Gold Electrode Arrays for Bioelectronic Interfaces (Adv. Funct. Mater. 7/2016). (February 2016) - Khan, Yasser; Pavinatto, Felippe J.; Lin, Monica C.; Liao, Amy; Swisher, Sarah L.; Mann, Kaylee; Subramanian, Vivek; Maharbiz, Michel M.; Arias, Ana C.
Abstract : On page 1004, A. C. Arias and co‐workers demonstrate inkjet‐printed gold electrode arrays on plastic substrates—with a special focus on laser‐cut freestanding electrodes—that exhibit excellent mechanical compliance. Taking advantage of the low‐cost and large‐area manufacturing techniques, these mechanically flexible and chemically inert electrode arrays are promising for novel wearable medical sensing applications.